Alterations of Nedd4‐2‐binding capacity in PY‐motif of NaV1.5 channel underlie long QT syndrome and Brugada syndrome. (21st January 2020) - Wang, Ya; Du, Yuan; Luo, Ling; Hu, Peijing; Yang, Guodong; Li, Tao; Han, Xiu; Ma, Aiqun; Wang, Tingzhong
Abstract: Aims: Pathogenic variants of the SCN5A gene can cause Brugada syndrome (BrS) and long QT syndrome (LQTS), which predispose individuals to potentially fatal ventricular arrhythmias and sudden cardiac death. SCN5A encodes the NaV 1.5 protein, the pore forming α‐subunit of the voltage‐dependent cardiac Na + channel. Using a WW domain, the E3 ubiquitin ligase Nedd4‐2 binds to the PY‐motif ([L/P]PxY) within the C‐terminus of NaV 1.5, which results in decreased protein expression and current through NaV 1.5 ubiquitination. Here, we investigate the role of E3 ubiquitin ligase Nedd4‐2‐mediated NaV 1.5 degradation in the pathological mechanisms of the BrS‐associated variant SCN5A‐p.L1239P and LQTS‐associated variant SCN5A‐p.Y1977N. Methods and Results: Using a combination of molecular biology, biochemical and electrophysiological approaches, we examined the expression, function and Nedd4‐2 interactions of SCN5A‐p.L1239P and SCN5A‐p.Y1977N. SCN5A‐p.L1239P is characterized as a loss‐of‐function, whereas SCN5A‐p.Y1977N is a gain‐of‐function variant of the NaV 1.5 channel. Sequence alignment shows that BrS‐associated SCN5A‐p.L1239P has a new Nedd4‐2‐binding site (from LLxY to LPxY). This new Nedd4‐2‐binding site increases the interaction between NaV 1.5 and Nedd4‐2, enhancing ubiquitination and degradation of the NaV 1.5 channel. Disruption of the new Nedd4‐2‐binding site of SCN5A‐p.L1239P restores NaV 1.5 expression and function. However, the LQTS‐associated SCN5A‐p.Y1977N disrupts the usual Nedd4‐2‐binding site (from PPxY to PPxN). This decreases NaV 1.5‐Nedd4‐2 interaction, preventing ubiquitination and degradation of NaV 1.5 channels. Conclusions: Our data suggest that the PY‐motif plays an essential role in modifying the expression/function of NaV 1.5 channels through Nedd4‐2‐mediated ubiquitination. Alterations of NaV 1.5‐Nedd4‐2 interaction represent a novel pathological mechanism for NaV 1.5 channel diseases caused by SCN5A variants.